Succession and Correlation of Ancient Greek, IX-XII Centuries. Central Asian and XIV-XVI Centuries European Philosophical Thought. / Sucesión y correlación del griego antiguo, siglos IX-XII. Asia central y siglos XIV-XVI en el pensamiento filosófico europeo - Shadmanov, Kurban B.; Baratova, Marifat; Kurbanova, Gulnoz; Shodiev, Shahobiddin; Khamraeva, Rohat (Utopía y Praxis Latinoamericana)
ABSTRACT The paper considers issues dealt with Central Asian philosophical thought of the IX-XIII centuries and its interdependence and interconnection of the XIV-XVI centuries European Medieval and Renaissance philosophy. The author tries to find out appropriate answers to the questions put by sharing a bit of historical excurse in to the history of the East-West philosophy succession and correlation. The focus is to discover a major contribution of classical Central Asian philosophy of the IX-XII centuries to further development of the Middle Ages and the Renaissance philosophical thought of Europe. RESUMEN El artículo examina cuestiones relacionados con el pensamiento filosófico de Asia Central de los siglos IX-XIII y su interdependencia e interconexión con la filosofía medieval y renacentista europea de los siglos XIV-XVI. Los autores intentan encontrar respuestas apropiadas a las preguntas hechas al hacer un poco de excursión histórica en la historia de la sucesión y correlación de la filosofía este-oeste. El objetivo es descubrir una contribución importante de la filosofía Central asiática clásica de los siglos IX-XII para el desarrollo adicional de la Edad Media y el pensamiento filosófico del renacimiento de Europa.